THE IMPACT ANALYSIS OF JOB SATISFACTION, WORK MOTIVATION, AND LOYALTY ON PERFORMANCE IMPROVEMENT AT ÉCLAT BEAUTÉ HOUSE - Lestari, Maudy; Pratama, Siswa; Ario, Firman (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2024)
This study aimed to determine the influence of job satisfaction, work motivation, and loyalty on performance improvement at Éclat Beauté House. This research was quantitative in nature. Data collection techniques were conducted through observation and questionnaire completion. Data analysis techniques employed multiple linear regression analysis with the assistance of SPSS version 25. The sample for this research consisted of 30 employees of Éclat Beauté House. Simultaneously, variables X1, X2, and X3 (job satisfaction, work motivation, and loyalty) simultaneously had a positive and significant influence on performance improvement at Éclat Beauté House Medan. It is stated as positive because if job satisfaction, work motivation, and loyalty improve, performance improvement will also increase. Conversely, if job satisfaction, work motivation, and loyalty decline, performance improvement will decrease as well.